Fractional‐order PID servo control based on decoupled visual model. (28th November 2018) - Liu, Weipeng; Bian, Gui‐Bin; Rahman, Muhammad Rameez Ur; Zhang, Haojie; Chen, Haiyong; Wu, Wanqing
Summary: A decoupled visual model and a fractional PID controller are designed aiming at the problem of the view distortion in the fillet weld welding process. Firstly, the intersection point coordinates of two laser stripes are selected as the image characteristics, and the decoupled visual model is designed to the tracking control of the fillet weld seam so that the control value in two directions is decoupled, reducing the difficulty of control. In addition to this, the image may produce distortion in the dynamic tracking process, causing nonlinearity and coupling in two directions. To solve this problem, the fractional‐order PID controller is designed so that the adjustment range and the control ability are improved better than the traditional PID controller. Some experiments verify that the desired performance can be achieved by using the proposed methods.